Transformasi Pembelajaran IPA SD Kelas 4: Meningkatkan Kreativitas dan Hasil Belajar Siswa melalui Media Digital Interaktif WordWall dengan Pendekatan Kontekstual - Syarif, Ahmad; Hariyani, Mimi (Journal of Practice Learning and Educational Development, 2026)
The limited availability of engaging and contextual learning media remains a challenge in science education at the elementary school level. This has an impact on low creativity and learning outcomes among students. This study aims to develop WordWall-based digital media integrated with the Contextual Teaching and Learning (CTL) approach to improve creativity and learning outcomes among students on the subject of animal classification based on their food types in the fourth grade of elementary school. The method used was Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). The research subjects were fourth-grade elementary school students. Data collection techniques included interviews, expert validation questionnaires, student assessment questionnaires on the media, and practicality questionnaires. The data were analyzed descriptively, quantitatively, and qualitatively. The validation results showed that the media met the validity criteria with an average score of 85% for content, 90% for language, and 95% for visual appearance, with an instrument reliability value of 0.872. Student assessment of the media showed an average score of 3.35 on a scale of 4 (good category) with a Cronbach's Alpha of 0.948. The practicality test obtained an average score of 3.21 (good category) with a reliability value of 0.931. These findings indicate that CTL-based WordWall media is feasible, practical, and effective for use in science learning in elementary schools.